A Novel Side‐Chain Liquid Crystal Elastomer Exhibiting Anomalous Reversible Shape Change. Issue 35 (25th June 2020) - Yin, Lu; Han, Li; Ge, Feijie; Tong, Xia; Zhang, Wei; Soldera, Armand; Zhao, Yue
Abstract: Liquid crystalline elastomers (LCEs) have been actively investigated as stimuli‐controlled actuators and soft robots. The basis of these applications is the ability of LCEs to undergo a reversible shape change upon a liquid crystalline (LC)‐isotropic phase transition. Herein, we report the synthesis of a novel LCE based on a side‐chain liquid crystalline polymer (SCLCP). In contrast to known LCEs, this LCE exhibits a striking anomalous shape change. Subjecting a mechanically stretched monodomain strip to LC‐disorder phase transition, both the length and width of the strip contract in isotropic phase, and both elongate in LC phase. This thermally induced behaviour is the result of a subtle interplay between the relaxation of polymer main chain oriented along the stretching direction and the disordering of side‐group mesogens oriented perpendicularly to the stretching direction. This finding points out potential design of LCEs of this peculiar type and possible applications to exploit. Abstract : A liquid crystalline elastomer strip can expand in both length and width on cooling and shrink along the two directions on heating over order–disorder phase transition.